As temporalidades que caracterizam a agricultura familiar do município de Marmeleiro (PR) - Braga, Luís Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this research, they are identified the changes and continuities in agricultural production in the borough of Marmeleiro, after deployment and continued expansion of so-called modernization of agriculture, through the analysis of temporality. For this, we identified the different rhythms of time present in agricultural production, both slow as the fastest through the study of space-time relationship, which leads to understanding the territory, the territoriality and temporality. The agricultural modernization process did not break completely with the modes of production that existed, this process was not smooth, established a standard production a rhythm of time that affected / disorganized most agricultural production systems, but has not provided the conditions for everyone to reach this production level. To analyze this heterogeneity of situations, we used an approach of temporality, listing the time rhythms with the levels of integration and mechanized farmers in the municipality of Marmeleiro, Paraná Southwest. The city has, according to the Brazilian Institute of Geography and Statistics (IBGE, 2006), in 1404 agricultural establishments and an agriculture based on family farms with small areas of land. Through empirical work, they interviewed 203 farmers, dividing them into three groups, in rural communities, because they have internal similarities. Therefore, we will demonstrate the rhythms of time; the changes and continuities; the different conditions of production; of life and future prospects. We analyzed the poultry and smoke from the system integration, the production of (soybean and corn), milk production and production for family consumption, demonstrating how these productions modify the pace of time farmers relatives...

Nesta pesquisa, são identificadas as modificações e permanências na produção agropecuária do município de Marmeleiro, após a implantação e contínua expansão da chamada modernização da agricultura, através da análise das temporalidades. Para isso, identificaram-se os diferentes ritmos de tempo presentes na produção agropecuária, tanto os lentos como os mais rápidos, através do estudo da relação espaço-tempo, que leva a compreender o território, as territorialidades e as temporalidades. O processo de modernização da agricultura não rompeu totalmente com os modos de produções que existiam, esse processo não foi homogêneo, estabeleceu-se um padrão de produção um ritmo de tempo que afetou/desorganizou a maioria dos sistemas de produção agropecuária, porém não proporcionou as condições para todos alcançarem esse patamar de produção. Para análise dessa heterogeneidade de situações, utilizou-se uma abordagem das temporalidades, relacionando os ritmos de tempo com os níveis de integração e mecanização dos agricultores, no município de Marmeleiro, Sudoeste do Paraná. O município possui, segundo dados do Instituto Brasileiro de Geografia e Estatística (IBGE, 2006), 1404 estabelecimentos agropecuários e uma agricultura baseada na produção familiar com pequenas áreas de terra. Através do trabalho empírico, foram entrevistados 203 agricultores, dividindo-os em três grupos, por comunidades rurais, pois estas têm semelhanças internas. Com isso, demostrar-se-á os ritmos de tempo; as mudanças e permanências; as diferentes condições de produção; de vida e de perspectivas futuras. Analisou-se a produção de aves e fumo, a partir do sistema de integração, a produção de grãos (soja e milho), a produção de leite e a produção para o consumo familiar, demonstrando como essas produções modificam o ritmo de tempo dos agricultores familiares...
Keywords: Geografia; Agricultura familiar; Mecanização agrícola; Territorialidade humana; Agropecuaria; Geografia agrícola; Tempo; Geography